Association of socioeconomic status with diabetic microvascular complications: a UK Biobank prospective cohort study - Yikeng Huang; Zhi Zheng; Haibing Chen; Chufeng Gu (Diabetology & Metabolic Syndrome)
Abstract Background Prior studies on the link between socioeconomic status (SES) and diabetic microvascular complications have been inconclusive. This study aimed to explore whether SES is associated with the risk of diabetic retinopathy (DR), nephropathy (DN) and diabetic peripheral neuropathy (DPN) using large prospective cohort. Methods SES was evaluated using education attainment (individual level), household income (household level), and Townsend deprivation index (TDI, neighborhood level). This study included 28,339 participants without DR, 29,951 without DN and 29,762 without DPN at baseline from the UK Biobank. Weighted Cox proportional hazard models were used to investigate the relationship between SES and the risk of diabetic microvascular complications. Results The median follow-ups of the DR, DN and DPN cohorts were 12.95, 12.89 and 13.02 years, respectively. In total, 3,177 (11.2%) participants developed DR, 4,418 (14.8%) developed DN and 1,604 (5.4%) developed DPN. After adjusting for confounders, higher education levels (DN: hazard ratios [HR] = 0.85; 95% CI, 0.82–0.89; P < 0.001; DPN: HR = 0.93; 95% CI, 0.87-1.00; P = 0.040), higher household income (DN: HR = 0.80; 95% CI, 0.75–0.85; P < 0.001; DPN: HR = 0.80; 95% CI, 0.73–0.89; P < 0.001), and lower TDI (DN: HR = 1.19; 95% CI, 1.14–1.23; P < 0.001; DPN: HR = 1.27; 95% CI, 1.19–1.36; P < 0.001) were associated with a lower risk of DN and DPN. In contrast, a lower risk of DR was only related to higher household income (HR = 0.92; 95% CI, 0.87–0.97; P = 0.004) and lower TDI (HR = 1.08; 95% CI, 1.02–1.13; P = 0.004). Conclusions Low SES increases the risk of diabetic microvascular complications, emphasizing the need for equitable medical resource allocation to reduce diabetes-related inequity.